PENGEMBANGAN ALAT PERAGA SISTEM PENCERNAAN UNTUK SEKOLAH DASAR - Roby Zulkarnain Noer (Biopedagogia, 2021)
Abstract: Learning science for elementary school students is a difficult thing. Especially when the concept of learning is abstract. One example is material related to the digestive system. Therefore, it is necessary to develop a learning model that can show parts of the digestive system. The purpose of this study was to develop a model of the digestive system in elementary schools. This research uses research and development research. The results showed that the overall data from material expert validation, media expert validation, limited trial, main field trial, and operational field trial could conclude the feasibility of learning media for the human digestive system in class V SDN Utama 2 Tarakan is very feasible. Keywords: digestive system, media